Harmonizing Access to Justice and Legal Protection for Victims of Sexual Violence with Intellectual Disabilities - Sarah Fitri Salsabillah; Reva Arfika Sukma; Luthfiyya Layalia Azzahra; Muhammad Amar Adni Bin Mukhairil Azni; Suwidia Indah Indriyani (Disable, 2025)
Victims of sexual violence involving people with intellectual disabilities face two major barriers in Indonesia’s criminal justice system: a high risk of victimization and limitations in giving effective testimony. Although Indonesia’s substantive legal framework guarantees protection for persons with disabilities, implementation is hindered by procedural rigidities in the Criminal Procedure Code (KUHAP). This gap between normative rights and procedural practice risks procedural discrimination that obstructs access to justice. Using a normative juridical method with statutory, conceptual, and comparative approaches, this study examines KUHAP, national disability-related instruments, and Malaysian legal instruments. Findings show Indonesia still relies heavily on law enforcement discretion to provide procedural accommodations, while Malaysia has adopted more adaptive mechanisms such as live-link testimony, intermediaries, and admissible pre-recorded statements. As a novelty, this study proposes a procedural harmonization model: expanding the definition of witness, mandating special counsel involvement, and implementing trauma-informed individual assessments in KUHAP. This model aims to strengthen equal, inclusive, and non-discriminatory access to justice for victims with intellectual disabilities in Indonesia’s criminal justice system.